A contribution to ethnobotany and review of phytochemistry and biological activities of the Iranian local endemic species Sclerorhachis leptoclada Rech.f. - Mohammadi, Toktam; Pirani, Atefeh; Vaezi, Jamil; Moazzeni, Hamid (Ethnobotany Research and Applications, 2020)
Background: Sclerorhachis leptoclada Rech.f. is endemic to the South Khorassan province in east of Iran. Although S. leptoclada has been widely used as medicinal and edible plant by indigenous people, its ethnobotanical uses have not been well documented yet. This study presents the results of an ethnobotanical survey and reviews phytochemistry and biological activities of S. leptoclada. Methods: The ethnobotanical study was conducted in Birjand and adjacent areas between March 2018 and December 2019. During this survey, 58 local people were interviewed using a semi-structured questionnaire. The ethnobotanical data were analyzed by using indices Fidelity Level (FL) and Relative Frequency of Citation (RFC). In addition, the available scientific literatures were reviewed to avail the information on phytochemistry and biological activities of Sclerorhachis leptoclada. Results: The present study revealed the folklore uses of Sclerorhachis leptoclada for different purposes such as increasing lactation, blood purification, treating digestive disorders, headache, body pains, herpes, and cold. The literature review showed that a total of 57 compounds have been isolated from S. leptoclada. Conclusions: Variety of ethnomedicinal uses of Sclerorhachis leptoclada highlights its notable pharmacological potential. However, further tests on its bioactivity, active phytochemicals, and their mechanisms of action are needed to ensure a safe use. The limited distribution of the plant and excessive harvesting of the aerial plant parts necessitate educating local people to conserve populations of this local endemic species. Keywords: Asteraceae, ethnobotany, Iran, medicinal plants, Sclerorhachis